Analisis Rasio Keuangan PT Kereta Api Indonesia (Persero) Periode 2022-2023 Berdasarkan Rasio Likuiditas - Tiara, Fadilla Siska; Sulastri, Eva Maria (BUDGETING : Journal of Business, Management and Accounting, 2024)
This study assesses an organization's financial performance using financial statements from different reporting periods. The financial statements of a business can aid in decision-making and asset growth for the general public, investors, shareholders, and management. This study investigates the financial performance of PT Kereta Api Indonesia (Persero) and its Subsidiaries in 2022-2023. This quantitative descriptive research uses secondary data as a data source. Internal data is used, and data collection methods include documentation and literature studies. The study uses financial measures consisting of liquidity ratios: Current Ratio, Quick Ratio, and Cash Ratio. Keywords: Company Performance, Financial Analysis, Liquidity Ratio